Polymer membranes with enhanced stability to biofouling - Vakuliuk, Polina; Furtat, Iruna; Yatseyko, O. (My University, 2018)
The major problem in membrane separations is biofouling as it leads to more frequent chemical cleaning, higher operating pressures, shortened membrane life, and compromised product water quality. Methods of creation of new polymer composite membranes with increased resistance to biofounling by bulk and surface modification of membranes have been developed, separation and functional properties of the received membranes have been investigated. The performed researches allowed to create a number of new functionalized membranes with a wide range of properties and to improve the technological processes of obtaining hydrophilic, charged and bactericidal polymer membranes to increase their usage for water treatment, concentration and separation of substances of different nature.Основною проблемою в процесах мембранного розділення є біозабруднення мембран, адже це призводить до підвищення робочих тисків, скороченого терміну експлуатації мембран, необхідності очищення мембран тощо. Розроблені методики створення нових полімерних композитних мембран з підвищеною стійкістю до біозабруднення за допомогою об’ємного та поверхневого модифікування мембран та досліджені розділові та функціональні властивості одержаних мембран. Виконані дослідження дозволили створити низку нових функціалізованих мембран з широким діапазоном властивостей і удосконалити технологічні процеси одержання гідрофільних, заряджених та бактерицидних полімерних мембран для підвищення ефективності їх використання в галузях водопідготовки, концентрування та розділення речовин різної природи.
Keywords: polymer membranes; biofouling; bulk and surface modification; полімерні мембрани; біозабруднення; об’ємне і поверхневе модифікування